Cultivation of different seaweed species and seasonal changes cause divergence of the microbial community in coastal seawaters - Xu, Ningning; Wang, Wenlei; Xu, Kai; Xu, Yan; Ji, Dehua; Chen, Changsheng; Xie, Chaotian (Frontiers in Microbiology, 2022)
Although the effects of certain species of seaweed on the microbial community structure have long been a research focus in marine ecology, the response of the microbial community to seasons and different seaweed species is poorly understood. To understand microbiome diversity, community structure, interactions, and functions according to seaweed species and seasons, a total of 39 seawater samples from different zones and growth periods during a period of three months were collected from Neoporphyra haitanensis cultivation zones (P), Gracilaria lemaneiformis-Saccharina japonica mixed cultivation zones (G), and control zones (C). These samples were then analyzed using 18S and 16S rRNA gene sequencing to ascertain the fungal and bacterial communities, respectively, along with the determination of environmental factors. Our results showed that the variability of eukaryotic and prokaryotic microbial communities was predominantly shifted by increased dissolved oxygen (DO), decreased inorganic nutrients, and dissolved organic matter (DOM) released from seaweed. Certain microbial groups such as Aurantivirga, Pseudomonas, and Woesei were stimulated and enriched in response to seaweed cultivation, and the enriched microorganisms varied across seaweed cultivation zones due to differences in the composition of released DOM. In addition, seasonal changes in salinity and temperature were strongly correlated with microbial community composition and structure. Our study provides new insights into the interactions between seaweed and microbial communities.